Formation Of Qualified Bachelor Through Soft Skills In Extracurricular Activities Of University Of Muhammadiyah Sumatera Utara Students - Ahmad i Zulfiqar Shah Abdul Had; A Akrim (UMSU, 2020)
Referring to Government Regulation No. 30 of 1990 concerning Higher Education as an elaboration of Law No. 2 of 1989 concerning the National Education System which states that the aim of national education is to form a whole person. But in its implementation, the implementation of tertiary institutions places too much emphasis on the cognitive or academic aspects of higher education institutions. To improve the ability of instructors from the Universitas Muhammadiyah Sumatera Utara (UMSU) to conduct Training of Trainers with experts from the Higher Education. The implementation often clashes with the lecture schedule. The schedule for implementing soft skills training often clashes with the schedule of college students. But these problems can be overcome by collaborating and asking for permission from the faculty so that the student can take part in soft skills training. Involving as many lecturers as possible with Masters (S2) and Doctors (S3) degrees by providing debriefing. UMSU is the largest private university in North Sumatra, thus the indicators of soft skills success should be used as benchmarks for other private universities that have not had the opportunity to develop soft skills.Keywords: Bachelor, Soft skills, Extracurricular